POPULATION, EDUCATION AND MAQAṢID-BASED HUMAN DEVELOPMENT IN INDONESIA: EVIDENCE FROM PROVINCIAL PANEL DATA WITH ECONOMIC GROWTH MODERATION (2016–2023) - Mardiyatillah, Sakinah; Hutagalung, Abdul Jalil (Islamic Economics Program, Faculty of Islamic Economics and Business, 2025)
This study seeks to ascertain the extent to which economic growth can directly and indirectly influence the Human Development Index (HDI), as well as the roles of population and education in this context. The findings indicate that both population and education significantly contribute to the Human Development Index (HDI), as evidenced by the test results. While moderating interactions do not exert a significant influence, they do not alter the relationship between population and education concerning the Human Development Index (HDI). The conclusion underscores the necessity of balancing population growth with enhancements in educational quality to foster a positive shift in the Human Development Index (HDI), which, in turn, will impact economic growth both directly and indirectly.